Педагогик-психологик тадқиқотларда жисмоний тарбия ва спорт бўйича мутахассисларни касбий компетентлилигини ошириш масалалари - Расулов, З.П (FAN va JAMIYAT, 2023)
This article is devoted to the topic of the professional potential of future sports coaches. Also in the text of the article, some theoretical studies of psychological and pedagogical qualities explaining the potential of the coach are analyzed. In the analysis of scientific concepts and scientific concepts presented in the article, the scientific sources presented in the application were taken as the basis.